Total Quality Management: Insight from Donyma Steel Complex, Ghana. - Adusei, Charles; Bimpeh, Peter Karikari (Archives of Business Research, 2016)
Total Quality Management (TQM) is considered a very important factor for the long-term success of an organisation. Service quality is a major component of TQM. This paper ascertains whether service quality leads to customer satisfaction and what accounts for that at Donyma Steel Complex. The study uses survey data from staffs and customers to explain issues on TQM and challenges associated with total quality service. Results revealed mean of 4.00 and standard deviation of 0.577 of respondents, which supports the notion that high performing department(s) share strategies with other departments. The only negative gap score was on a component of reliability. Difficulty in changing the standpoint of staff on quality had the highest mean of 3.84 as the key challenge of TQM implementation. It is recommended that measures and policies that promote cordial relationship should be encouraged to enhance TQM practices and management should target service quality dimensions that had a low score as a starting point of improving service quality.